Hybrid solar cells from water-soluble polymers - James T. McLeskey; Qiquan Qiao (International Journal of Photoenergy)
We report on the use of a water-soluble, light-absorbing polythiophene polymer to fabricate novel photovoltaic devices. The polymer is a water-soluble thiophene known as sodium poly[2-(3-thienyl)-ethoxy-4-butylsulfonate] or PTEBS. The intention is to take advantage of the properties of conjugated polymers (flexible, tunable, and easy to process) and incorporate the additional benefits of water solubility (easily controlled evaporation rates and environmentally friendly). The PTEBS polythiophene has shown significant photovoltaic response and has been found to be effective for making solar cells. To date, solar cells in three different configurations have been produced: titanium dioxide (TiO2) bilayer cells, TiO2 bulk heterojunction solar cells, and carbon nanotubes (CNTs) in bulk heterojunctions. The best performance thus far has been achieved with TiO2 bilayer devices. These devices have an open circuit voltage (Voc) of 0.84V, a short circuit current (Jsc) of 0.15 mA/cm2, a fill factor (ff) of 0.91, and an efficiency (η) of 0.15 %.